2021
DOI: 10.1080/13683500.2021.1924634
|View full text |Cite
|
Sign up to set email alerts
|

Understanding destination brand love using machine learning and content analysis method

Abstract: This study aims to apply the concept of brand love in tourist destinations in order to identify the core-elements that could have influential impacts on generating destination brand love. This has been carried out by using a mixed-method of machine learning and content analysis. We have discovered that the topics have been generated for historical landmarks and destinations by analyzing the visitors' on-line reviews are architecture, historical sites, tradition and shrine places, which could be similar to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
1
5
0
1
Order By: Relevance
“…Content analysis began to use computer assistance as early as the 1960s (Tausczik & Pennebaker, 2010;Pollach, 2012), which was defined as systematic and detailed analysis of different types of data to identify latent meanings, themes, and assumptions (Seyyedamiri et al, 2021). In social sciences, the content analysis produced a valid and reliable measurement of the frequency (and, sometimes, intensity) with which a concept occurred (Budak et al, 2021).…”
Section: Content Analysis Methods Less Discussedmentioning
confidence: 99%
“…Content analysis began to use computer assistance as early as the 1960s (Tausczik & Pennebaker, 2010;Pollach, 2012), which was defined as systematic and detailed analysis of different types of data to identify latent meanings, themes, and assumptions (Seyyedamiri et al, 2021). In social sciences, the content analysis produced a valid and reliable measurement of the frequency (and, sometimes, intensity) with which a concept occurred (Budak et al, 2021).…”
Section: Content Analysis Methods Less Discussedmentioning
confidence: 99%
“…Therefore, historical and cultural features have become core elements to build WHSs’ brand. Visitors’ online reviews reflect their focus on architecture, historical sites, traditions and shrine places of historical destinations (Seyyedamiri et al , 2022). Similarly, national parks possess unique geographical boundaries and regional characteristics, and social media has become an important way to understand place meaning (Marcotte and Stokowski, 2021), visitors’ connectedness (Zhang et al , 2023), characteristics (Kong et al , 2023) and visitor activities (Huang, 2023).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Swanson (2017) identified three categories of destination brand love: friendship, affection, and romantic. Filieri et al (2021) and Seyyedamiri et al (2022) studied destination brand love using social media postings and found that destination attributes are critical for tourists to build destination brand love. Amaro et al (2020) found that student exchange program experience and destination image have positive effects on destination brand love, which in turn leads to word-of-mouth, recommendation, and revisit intention.…”
Section: Destination Brand Lovementioning
confidence: 99%